Studies on Physical, Mechanical & Tribological Properties of Al6063 Incorporated with CNT & Nano Clay as Filler Materials - Asifiqbal M. Doddamani; Iresh G.Bhavi; R. Noorahmed; Mohan B. Vanarotti; J. Balaji; Syed Sameer Hussain (Tribology in Industry)
In order to improve mechanical and tribological qualities, this study investigates the innovative use of stir-casting to integrate carbon nanotubes (CNT) and nano clay (NC) as dual reinforcement materials in Al6063 matrix composites. Combining CNT (0–2%) with NC (0–2%) in a synergistic way presents a special chance to capitalise on each filler material's particular properties. With an increase in CNT and NC on the Al6063 matrix, mechanical parameters like tensile strength, hardness, flexural strength, and compressive strength rise from 225-245 MPa, 45-74 BHN, 218-298 MPa, and 140-152 MPa. Tribological characteristics were analyzed through pin on disc (tribometer), with varying loads (5 N - 10 N), velocity (0.209 m/s - 1.047 m/s) and sliding distance (253.32-753.98 m). The results demonstrate that the addition of 2 wt% CNT and 2 wt% NC reduces the specific wear rate value and increase the coefficient of friction. A decrease of wear rate value 0.0162 mm3/m and increase in COF 0.70 was observed at maximum load of 10 N and velocity of 0.209 m/s corresponding to 2 wt% of CNT and NC incorporation. The homogeneous distribution of fillers in the metal matrix, tensile fracture, distinct wear modes, and the importance of CNT/NC in changing the wear process from abrasion to delamination are all demonstrated by SEM analysis.